Percepciones y expectativas previas al tratamiento de ortodoncia en pacientes con indicación de cirugía ortognática en una escuela de postgrado (2023)
Orthognathic surgery takes into account different procedures designed to correct dental, skeletal and facial discrepancies. All of these procedures can improve musculoskeletal function while improving appearance, impacting quality of life and psychosocial well-being. Within the most common indications for orthognathic surgery we could classify them as facial esthetics, dental esthetics, functional occlusion and skeletal discrepancies in the three planes of space (sagittal, transverse and vertical).